2016
DOI: 10.3390/ijms17081282
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 Mediates Augmented CD40 Expression in Bone Marrow Derived Plasmacytoid Dendritic Cells in Symptomatic Lupus-Prone NZB/W F1 Mice

Abstract: Systemic lupus erythematosus (SLE) is a chronic multi-organ autoimmune disease characterized by hyperactivated immune responses to self-antigens and persistent systemic inflammation. Previously, we reported abnormalities in circulating and bone marrow (BM)-derived plasmacytoid dendritic cells (pDCs) from SLE patients. Here, we aim to seek for potential regulators that mediate functional aberrations of pDCs in SLE. BM-derived pDCs from NZB/W F1 mice before and after the disease onset were compared for toll-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Similarly, using the common mDCs markers CD11c and CD11b [26], a distinct population of CD11c hi CD11b + cells constitutively expressing high levels of MHC class II and the costimulatory molecule CD80 could be identified (Figure 1B). Using these markers, the frequency and total number of pDC and CD11c hi CD11b + mDC were compared in BWF1 mice before and after symptomatic SLE onset, which was marked by an increase in anti-dsDNA antibody level and the manifestation of proteinuria [27]. Results showed that there was a lower splenic pDCs frequency in symptomatic (Sym) mice when compared with pre-symptomatic (Pre-Sym) mice (0.48 ± 0.04% VS. 1.15 ± 0.06%, p ≤ 0.0001) (Figure 1C), while this difference was not observed in age- and sex-matched non-lupic parental NZW strain (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, using the common mDCs markers CD11c and CD11b [26], a distinct population of CD11c hi CD11b + cells constitutively expressing high levels of MHC class II and the costimulatory molecule CD80 could be identified (Figure 1B). Using these markers, the frequency and total number of pDC and CD11c hi CD11b + mDC were compared in BWF1 mice before and after symptomatic SLE onset, which was marked by an increase in anti-dsDNA antibody level and the manifestation of proteinuria [27]. Results showed that there was a lower splenic pDCs frequency in symptomatic (Sym) mice when compared with pre-symptomatic (Pre-Sym) mice (0.48 ± 0.04% VS. 1.15 ± 0.06%, p ≤ 0.0001) (Figure 1C), while this difference was not observed in age- and sex-matched non-lupic parental NZW strain (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…These lines were maintained and interbred to generate F1 generation (BWF1) in the Minimal Disease Area of the Laboratory Animal Unit, The University of Hong Kong. Disease development in BWF1 was assessed by monitoring serum level of anti-dsDNA IgG and development of proteinuria, as previously described [27]. Mice between 8 and15 weeks old without an increase in anti-dsDNA IgG (level comparable to the non-lupus parental strain NZW) and negative for proteinuria were defined as pre-symptomatic mice, while mice above 20 weeks old with elevation of anti-dsDNA IgG (level higher than two standard deviations of mean serum level in NZW) and proteinuria development (3mg/mL or above) for at least two consecutive weeks were defined as symptomatic mice.…”
Section: Methodsmentioning
confidence: 99%
“…Current studies have shown that dysregulated cell death contributes to SLE by increasing availability, pathogenic modifications, and abnormal processing and presenting of self-antigens. Epigenetic modifications involve this complex process at different levels, including triggering apoptosis at the initial phase, induction of impaired clearance of apoptotic materials by inappropriate DNA methylation, and aberrant antigen presentation or IFN-α production by DCs [ 93 ]. To induce the apoptosis of over-activated immune cells, recombinant PD-L1Ig has been proposed as a therapy in lupus [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells from poorly controlled patients with type I diabetes exhibit increased mRNA levels of the functional type I isoform of CD40 (60). It is not known whether changes in micro RNA that control CD40 transcription [i.e., miR-155, miR-424, miR-503 (61,62)] explain the upregulation of CD40 mRNA. In addition, CD154 protein levels are elevated in the blood from patients with diabetic microangiopathy and mice with diabetes (7,63,64).…”
Section: Cd40 In the Development Of Diabetic And I/r-induced Retinopamentioning
confidence: 99%